Mineral Status of Dairy Animals in Pulwama District of Jammu and Kashmir - Ashraf, A.; Sheikh, G.G.; Ganai, A.M.; Reshi, P.A. (Indian Journal of Animal Nutrition, 2022)
A total of 206 samples of blood were collected from crossbred jersey dairy cows of Pulwama district of Kashmir Division to assess the blood plasma mineral status with respect to the stage of lactation and milk yield parity. Macro-minerals (Ca, P, Mg, Na and K) were estimated by standard methods using commercial kits, whereas microminerals (Cu, Zn, Fe, Co and Mn) were estimated by atomic absorption spectroscopy (AAS). Significantly (P≤0.05) lower blood Ca, P, Mg and Na levels was reported in animals yielding milk upto above 10 kg followed 5-10 kg yielders and upto 5 kg and as compared to dry animals. Plasma P was recorded below critical levels in dairy animals of district Pulwama. There was no significant difference in mean plasma K levels of dairy animals among milk yielding and dry animals. Significant (P≤0.05) lower plasma Ca, P, Mg and Na levels were found in animals in early and mid-lactation stages of dairy animals compared to the late lactation stage with a non significant difference in plasma calcium levels in early and mid-lactation. Plasma micromineral (Cu, Zn, Fe and Co) concentration was reported significantly (P≤0.05) lower in high yielding animals (5-10kg and above 10kg) as compared to 0-5 kg yielders with the highest in dry animals. However, no significant difference was observed in plasma Mn level in dairy animals of district Pulwama in different production levels (above 10 kg, 5-10 kg, 5 kg yielders and dry) and at the stage of lactation (early, mid and late). The present study therefore indicates the need for the formulation of specific mineral mixtures for different stages of lactation.